2021
DOI: 10.1162/nol_a_00027
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neural Correlates of Speech Motor Sequence Learning in Stuttering and Neurotypical Speakers: An fMRI Investigation

Abstract: Stuttering is a neurodevelopmental disorder characterized by impaired production of coordinated articulatory movements needed for fluent speech. It is currently unknown whether these abnormal production characteristics reflect disruptions to brain mechanisms underlying the acquisition and/or execution of speech motor sequences. To dissociate learning and control processes, we used a motor sequence learning paradigm to examine the behavioral and neural correlates of learning to produce novel phoneme sequences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…Thus, speech planning processes or the coordination of articulators were not addressed to result in task-free functional connectivity changes. Our observation is in line with a recent neuroimaging study showing that PDS exhibit no deficit in learning to produce novel phoneme sequences (Masapollo et al, 2021); task-related fMRI data showed no difference in brain activity between PDS and controls for the articulation of practiced und novel pseudowords. Thus, sensorimotor learning and feedback processing in the context of voice control may be the main drivers of the neuroplasticity in the current study.…”
Section: Connectivity Changes Involve Brain Hubs Of the Sensorimotor Integration Networksupporting
confidence: 93%
“…Thus, speech planning processes or the coordination of articulators were not addressed to result in task-free functional connectivity changes. Our observation is in line with a recent neuroimaging study showing that PDS exhibit no deficit in learning to produce novel phoneme sequences (Masapollo et al, 2021); task-related fMRI data showed no difference in brain activity between PDS and controls for the articulation of practiced und novel pseudowords. Thus, sensorimotor learning and feedback processing in the context of voice control may be the main drivers of the neuroplasticity in the current study.…”
Section: Connectivity Changes Involve Brain Hubs Of the Sensorimotor Integration Networksupporting
confidence: 93%
“…The required number of cortico-cortical connections (black arrows) has decreased substantially, having been replaced by subcortical communications through the cerebellum (green arrows) and basal ganglia (red arrows). Evidence for speech learning-related reductions in processing load has been demonstrated by neuroimaging studies of nonnative consonant cluster learning (Segawa, Tourville, Beal, & Guenther, 2015;Masapollo et al, 2021).…”
Section: Phonological Content Buffering In Lateral Prefrontal Cortexmentioning
confidence: 98%
“…In a recent study combining speech motor training of novel phoneme sequences and brain imaging (fMRI), Masapollo et al (2021) found indications that people who stutter do not differ from typically fluent persons in terms of the ability to learn new speech motor sequences, but show impairments in the execution of the learned sequences. In addition, they observed an association between high level of in-scanner speech disfluencies and low activation of left basal ganglia sites.…”
Section: Discussionmentioning
confidence: 99%